1990
DOI: 10.2307/3869320
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of a Phenylalanine Ammonia-Lyase Promoter from Arabidopsis

Abstract: Phenylalanine ammonia-lyase (PAL) is encoded by a small family of genes in Arabidopsis. We cloned and partially characterized one of these genes, PAL1. The deduced amino acid sequence is highly similar to PAL from bean, parsley, and rice. The promoter contains sequence elements homologous to two putative regulatory elements conserved among severa1 phenylpropanoid genes. The regulation of the PAL1 gene was examined by analysis of P-glucuronidase (GUS) activity in transgenic Arabidopsis containing PAL1-GUS gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 11 publications
3
63
2
1
Order By: Relevance
“…The level of transcripts encoding phenylalanine am- monia lyase (PAL), the first enzyme in the phenylpropanoid pathway, also increased about 2-to 3-fold after wounding. The difference between our results and those ofOhl et al (26), who observed induction of PAL RNA 1 hr after wounding Arabidopsis plants, may be due to differences in the manner and severity of the wounding procedure. Not all amino acid biosynthetic pathways respond to wounding, because transcripts from ALS, the single-copy Arabidopsis gene encoding acetolactate synthase (25), an enzyme in the isoleucine-valine pathway, showed the same pattern of expression as DHS2 (Fig.…”
Section: Resultscontrasting
confidence: 57%
“…The level of transcripts encoding phenylalanine am- monia lyase (PAL), the first enzyme in the phenylpropanoid pathway, also increased about 2-to 3-fold after wounding. The difference between our results and those ofOhl et al (26), who observed induction of PAL RNA 1 hr after wounding Arabidopsis plants, may be due to differences in the manner and severity of the wounding procedure. Not all amino acid biosynthetic pathways respond to wounding, because transcripts from ALS, the single-copy Arabidopsis gene encoding acetolactate synthase (25), an enzyme in the isoleucine-valine pathway, showed the same pattern of expression as DHS2 (Fig.…”
Section: Resultscontrasting
confidence: 57%
“…In contrast to these find ings in tobacco is a recent report by Ohl et al [28] on transgenic Arabidopsis plants. These authors isolated one endogenous PAL prom oter, fused it to the ß-glucuronidase reporter gene, and found no expression in the root and shoot apices.…”
Section: Discussionmentioning
confidence: 69%
“…PAL was described in 1961 by Koukol and Conn (1) and has since been one of the most extensively studied enzymes in plants. Various structural and regulatory properties of PAL genes from bean (2-4), rice (5), parsley (6,7),Arabidopsis (8,9), potato (10), loblolly pine (11), pea (12,13), tomato (14), and poplar (15) have been reported. As far as analyzed, the number of PAL genes per haploid plant genome varies from 1 (11) to 5 (14), except for potato, which contains an unusually large family of "40-50 PAL genes (10).…”
Section: -Coumaratementioning
confidence: 99%